Implementasi Konsep Pendidikan Muhammadiyah dalam Upaya Membentuk Generasi Unggul Muhammadiyah - Iwantoro; Lilik Masruroh (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2020)
This study aims to describe the implementation of the concept of Muhammadiyah education at the secondary school level (SMA/SMK) to form a quality generation of Muhammadiyah in Pasuruan Regency and outline the supporting and inhibiting factors encountered in forming the quality generation. The researcher uses a qualitative approach, in which the researcher tries to describe as objectively as possible the findings in the field. This research was conducted in SMA/SMK Muhammadiyah under the auspices of the PD Muhammadiyah Dikdasmen Board of Pasuruan Regency. The schools are Muhammadiyah 4 Gempol High School, Muhammadiyah 3 Pandaan High School, Muhammadiyah 1 Pandaan Vocational School, and Muhammadiyah 2 Lekok Vocational School. Researchers conducted interviews with each of these institutions as well as conducting observations to photograph the state of education in the Muhammadiyah schools. The results showed that the Muhammadiyah schools had carried out education well in terms of formal service. These schools have a relatively small number of students compared to other schools because the focus on implementing the Muhammadiyah concept of education experiences obstacles besides that the majority of students have a Nahdlatul Ulama background '. The preparation of Muhammadiyah cadres from these schools could not be carried out optimally, so graduates from Muhammadiyah schools with other schools could be said to have almost the same characteristics. Supporting factors in the implementation of this educational process include; education staff, the majority of whom are still young, and have established cooperation with related parties. The inhibiting factors include; in put low students, educational facilities that do not meet standards, and community participation in operational financing less than the maximum. Key Words: The concept of Muhammadiyah, education, quality generation.